Level of ecological and economic diversification: a methodology for assessing the sustainability of agricultural enterprises - Strapchuk, Svitlana І.; Страпчук, Світлана Іванівна (My University, 2021)
As a global initiative within the framework of the United Nations Environment Programme framework, the Economics of Ecosystems and Biodiversity emphasises the importance of applying a systematic approach to the assessment of Natural Resources and the need to introduce new forms of economic growth to the sustainable development of enterprises. Existing management practices of agricultural enterprises, such as monoculture, create a constant monotonous load on the soil and lead to a decrease in humus content, contribute to erosion, but remain highly profitable. Changing the forms of economic growth in favour of introducing sustainable practices such as organic production, sustainable intensification, and eco-production requires appropriate sources of financing, a high level of environmental awareness, and comprehensive methods for assessing environmental and economic factors. The purpose of the study is to substantiate a methodological approach to a comprehensive assessment of the ecological and economic diversification of an enterprise based on the principles of sustainable development, which allows taking into account the level of diversity of cultivated crops in relation to the structure of marketable products. To achieve this goal, statistical information on the activities of agricultural enterprises in the Kharkivska Oblast was used, as well as monographic, graphical and statistical methods of research. Data analysis and processing were performed using specialised software: Microsoft Excel and Statistica 10. The study presents the developed and tested coefficient of ecological and economic diversification, which allows assessing the level of agrobiodiversity of sown areas and marketable products of agricultural enterprises based on the management results for 2019. The coefficient is based on information theory in the context of applying the Shannon-Weaver index. As a result of the search for the relationship between the coefficient of ecological and economic diversification and profit per 1 hectare, the statement about the gradual loss of profitability during the growth of the number of types of crops is confirmed. However, there are enterprises that maintain profitability during the expansion of the acreage structure. The practical significance of the findings obtained is allows assessing the possibility of adapting the structure of acreage to market conditions, taking into account environmental and economic factors. Економіка екосистем та біорізноманіття як глобальна ініціатива у межах Програми ООН з охорони навколишнього середовища підкреслює важливість застосування системного підходу до оцінювання природних ресурсів та необхідність впровадження нових форм економічного зростання, що забезпечить сталий розвиток підприємств. Наявні практики господарювання сільськогосподарських підприємств, такі як монокультура, створюють постійне одноманітне навантаження на ґрунти та призводять до зменшення вмісту гумусу, сприяють ерозії, проте залишаються високоприбутковими. Зміна форм економічного зростання на користь впровадження сталих практик на зразок органічного виробництва, сталої інтенсифікації, ековиробництва потребує відповідних джерел фінансування, високого рівня екологічної свідомості та комплексних методик оцінювання еколого-економічних чинників. Метою дослідження є обґрунтування методичного підходу до комплексної оцінки еколого-економічної диверсифікації підприємства на основі принципів сталого розвитку, що дозволяє врахувати рівень різноманіття вирощуваних культур у взаємозв’язку зі структурою товарної продукції. Для досягнення мети були використані дані діяльності сільськогосподарських підприємств Харківської області, а також монографічний, графічний та статистичний методи дослідження. Аналіз та обробка даних здійснювалися за допомогою спеціалізованих програм Microsoft Excel та Statistica 10. У роботі представлено розроблений та апробований коефіцієнт еколого-економічної диверсифікації, що дозволяє оцінити рівень агробіорізноманіття посівних площ та товарної продукції сільськогосподарських підприємств за результатами господарювання за 2019 рік. В основу коефіцієнта покладена теорія інформації в контексті застосування індексу Шеннона-Уівера. Унаслідок пошуку залежності між коефіцієнтом еколого-економічної диверсифікації та прибутком у розрахунку на 1 га, твердження щодо поступової втрати прибутковості під час зростання кількості видів вирощуваних сільськогосподарських культур підтверджено. Проте існують підприємства, які під час розширення структури посівних площ утримують прибутковість. Практична значимість отриманих результатів полягає в оцінці можливості адаптації структури посівних площ до ринкових умов із урахуванням екологічних та економічних чинників.
Рівень еколого-економічної диверсифікації: методика оцінювання аспекту сталості сільськогосподарських підприємст
Keywords: Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING; Research Subject Categories::SOCIAL SCIENCES::Business and economics; sustainable development; biodiversity; monoculture; agricultural enterprise; coefficient of ecological and economic diversification; economic effic; сталий розвиток; біорізноманіття; монокультура; сільськогосподарське підприємство; коефіцієнт еколого-економічної диверсифікації; економічна ефективність